2005
DOI: 10.1007/s00213-005-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoxetine and buspirone on the panicolytic-like response induced by the activation of 5-HT1A and 5-HT2A receptors in the rat dorsal periaqueductal gray

Abstract: The results suggest that facilitation of the 5-HT1A- and 5-HT2A-receptor-mediated inhibition of DPAG neuronal activity is implicated in the beneficial effect of antidepressants in panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 50 publications
(66 reference statements)
4
35
0
1
Order By: Relevance
“…As previously reported (de Bortoli et al 2006;Schutz et al 1985), our results showed that intra-dPAG injection of 5-HT, the preferential 5-HT2A receptor agonist DOI, or the 5-HT1A receptor agonist 8-OH-DPAT inhibited the expression of escape behavior evoked by electrical stimulation of the dPAG. They also showed for the first time that a high dose of the nonselective 5-HT2C receptor agonist mCPP or the preferential 5-HT2C ligand RO 60-0175 had similar inhibitory effects.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As previously reported (de Bortoli et al 2006;Schutz et al 1985), our results showed that intra-dPAG injection of 5-HT, the preferential 5-HT2A receptor agonist DOI, or the 5-HT1A receptor agonist 8-OH-DPAT inhibited the expression of escape behavior evoked by electrical stimulation of the dPAG. They also showed for the first time that a high dose of the nonselective 5-HT2C receptor agonist mCPP or the preferential 5-HT2C ligand RO 60-0175 had similar inhibitory effects.…”
Section: Discussionsupporting
confidence: 89%
“…Drug doses were based on previous studies carried out with the elevated T-maze and electrical stimulation of dPAG (Casarotto et al 2010;de Bortoli et al 2006;Nogueira and Graeff 1995;Schutz et al 1985;Zanoveli et al 2003Zanoveli et al , 2005Yamashita et al 2011). …”
Section: Escape Threshold Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…These lines of evidence may suggest the presence of diverse HTR2C populations, or, better, the expression of HTR2C receptors in the surface of interneurons embedded in inhibitory or facilitative pathways in the midbrain and limbic forebrain respectively. Antidepressant chronic treatment is effective against anxiety disorders, and it has been associated with modulation in the activity of HTR1A and HTR2A receptors in the midbrain [Mongeau and Marsden, 1997;Jacob et al, 2002;Zanoveli et al, 2005;de Bortoli et al, 2006;Zanoveli et al, 2007], whilst evidence for the HTR2C is sparse and divergent [Jacob et al, 2002;Moreira and Guimaraes, 2005] and further investigations are required. The other relevant structure within the midbrain is the SN, which receives afferences from the dorsolateral striatum, and directly projects to the thalamic motor nuclei.…”
mentioning
confidence: 99%